2015
DOI: 10.1139/cjfr-2014-0275
|View full text |Cite
|
Sign up to set email alerts
|

Reforestation and slope-position effects on nitrogen, phosphorus pools, and carbon stability of various soil aggregates in a red soil hilly land of subtropical China

Abstract: Abstract:The impact of slope position on forest restoration processes may dominate the interaction among topsoil aggregates, nutrients, and organic carbon (C) stability following reforestation on degraded hilly land. Six paired plots of shrubland and Masson pine (Pinus massoniana Lamb.) plantation reforested on shrubland were selected at different positions along a 25°slope in subtropical China. Soil and ecosystem nitrogen (N), phosphorus (P), and organic C stocks were quantified using a combination of excavat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
0
7
1
Order By: Relevance
“…The region has a subtropical moist monsoon climate, with a warm, dry summer and a cool, wet winter. The soil is Typic Hapludult Ultisols (locally “red soil”), which develops from Quaternary Red Clay and covers over 60% of 1.14 million km 2 of total land area in the southern China 48 . The average stand density, diameter at breast height and height of the selected Chinese fir plantation are approximately 1950 tree/ha, 10 cm and 9 m, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The region has a subtropical moist monsoon climate, with a warm, dry summer and a cool, wet winter. The soil is Typic Hapludult Ultisols (locally “red soil”), which develops from Quaternary Red Clay and covers over 60% of 1.14 million km 2 of total land area in the southern China 48 . The average stand density, diameter at breast height and height of the selected Chinese fir plantation are approximately 1950 tree/ha, 10 cm and 9 m, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The quantity of CO 2 produced was measured by titrating NaOH to pH 8.3 with 0.5 M HCl in the presence of BaCl 2 . The net amount of CO 2 produced from the soil or litter was calculated as the difference between the treatments and control jars 48 50 . Three replicates were applied for each treatment per incubation temperature.…”
Section: Methodsmentioning
confidence: 99%
“…In China alone, reforested plantations covered 69.33 million ha in 2014, becoming the largest around the world [27]. Although the influence of reforestation on deep soil OC is still poorly understood [22], deep soil carbon may be influenced by changes in land-use and/or management [28].…”
Section: Introductionmentioning
confidence: 99%
“…Globally, roughly 140 million hectares of land had been reforested before 2005, and reforestation has the potential to create more than 34 million hectares of forest by 2020 [ 4 ]. In China alone, reforested plantations covered 69.33 million ha in 2014, becoming the largest around the world [ 27 ]. Although the influence of reforestation on deep soil OC is still poorly understood [ 22 ], deep soil carbon may be influenced by changes in land-use and/or management [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…in the altitude, slope position, and slope exposure in the transition zone between the Loess Plateau and the Qinghai-Tibet Plateau is responsible for the heterogeneity of the microenvironment due to changing the light and water conditions, and affecting the soil texture, nutrient, vegetation diversity, and distribution (Xu et al 2020). Forests might be more prone to nutrition loss from hilltops (Zou et al 2014). The results of previous studies have suggested using strategies according to different topographic conditions of the Loess Plateau to maximize the benefits of afforestation, such as mitigating soil degradation and improving biodiversity (Taye et al 2013;X.…”
Section: Introductionmentioning
confidence: 99%